2019
DOI: 10.1186/s12885-019-5700-7
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-2 receptor/TMEM97 agonist PB221 as an alternative drug for brain tumor

Abstract: Background There are limited effective drugs that can reach the brain to target brain tumors, in particular glioblastoma, which is one of the most difficult cancers to be cured from. Because the overexpression of the sigma-2 receptor is frequently reported in glioma clinical samples and associated with poor prognosis and malignancy, we herein studied the anti-tumor effect of the sigma-2 receptor agonist PB221 (4-cyclohexyl-1-[3-(5-methoxy-1,2,3,4-tetrahydronaphthalen-1-yl)propyl]piperidine) on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…In addition, a high dose of PB221 induced cell death of ALTS1C1 cells; these effects all involved mitochondrial oxidative stress. Consistent with this notion, PB221 effectively retarded tumor growth in tumor models [19]. Using CRISPR/Cas9 technology to remove TMEM97 in HeLa cells, one recent study has found that TMEM97 does not mediate cytotoxicity induced by the sigma-2 ligand [25].…”
Section: Tmem97/sigma-2 Receptormentioning
confidence: 70%
“…In addition, a high dose of PB221 induced cell death of ALTS1C1 cells; these effects all involved mitochondrial oxidative stress. Consistent with this notion, PB221 effectively retarded tumor growth in tumor models [19]. Using CRISPR/Cas9 technology to remove TMEM97 in HeLa cells, one recent study has found that TMEM97 does not mediate cytotoxicity induced by the sigma-2 ligand [25].…”
Section: Tmem97/sigma-2 Receptormentioning
confidence: 70%
“…This green emitter compound was successfully used in flow cytometry and confocal microscopy analyses to visualize sigma-2 receptors ( Abate et al, 2014 ; Niso et al, 2015 ; Pati et al, 2017a ; Pati et al, 2018a ). Importantly, using this same strategy, also sigma-2 versus sigma-1 (and vice versa), selective ligands were obtained starting from the diverse pharmacophores identified through the years, such that fluorescent tracers to selectively study one sigma subtype at a time are also available ( Niso et al, 2015 ; Abate et al, 2016 ; Liu et al, 2019 ; Cantonero et al, 2020 ). In order to expand the fluorescent properties, the same scaffold adopted for F412 was used to decorate inorganic quantum dots (QDs) generating nanoparticles with superior fluorescent properties able to visualize sigma receptors ( Figure 5 ) ( Pati et al, 2018a ).…”
Section: Pb28: Structural Insightsmentioning
confidence: 99%
“…Mice were sacrificed when they deteriorated neurologically (failure to ambulate, lethargy) or after weight loss >20%. 31 Following transcardial perfusion with 5% sucrose and 4% paraformaldehyde in PBS, brain tissues were post-fixed with 4% paraformaldehyde overnight at 4°C and then transferred to 30% sucrose for dehydration. Brains were cryosectioned into 30-μm-thick slices.…”
Section: Immunohistology and Immunofluorescencementioning
confidence: 99%